Aplicación web responsiva para torneos de microfútbol comunales en el municipio de Soacha - Romero Murcia, Jorge Enrique; Prioló Flórez, Remberto Jose (Universidad Antonio Nariño, 2023)
The project focuses on the development of a web application for the efficient management of micro soccer tournaments in Bogota. Using Kanban methodology and MVC architecture, the application addresses the current problem of manual tournament management, offering a comprehensive solution. From team registration to match scheduling and results tracking, the application seeks to improve the experience for both participants and administrators. The adoption of modern web technologies and an inclusive approach to development reinforce innovation and usability. This project not only addresses a specific local need, but also lays the groundwork for future improvements in sports event management